540=b+3/2b+(b+45)

Simple and best practice solution for 540=b+3/2b+(b+45) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 540=b+3/2b+(b+45) equation:



540=b+3/2b+(b+45)
We move all terms to the left:
540-(b+3/2b+(b+45))=0
Domain of the equation: 2b+(b+45))!=0
b∈R
We multiply all the terms by the denominator
-(b+3+540*2b+(b+45))=0
We calculate terms in parentheses: -(b+3+540*2b+(b+45)), so:
b+3+540*2b+(b+45)
determiningTheFunctionDomain b+540*2b+(b+45)+3
Wy multiply elements
b+1080b+(b+45)+3
We get rid of parentheses
b+1080b+b+45+3
We add all the numbers together, and all the variables
1082b+48
Back to the equation:
-(1082b+48)
We get rid of parentheses
-1082b-48=0
We move all terms containing b to the left, all other terms to the right
-1082b=48
b=48/-1082
b=-24/541

See similar equations:

| 1/x(50)=25/ | | −3(1+6r)=14−r | | 12+8=10x+15 | | -3n+3(n-6)=-8+5n | | _3n+3(n-6)=-8+5n | | a-6=-39 | | 4=2+1.1x-0.1x^2 | | 4+2(1+x)=12x | | 7(2e+1)-3=6+6e | | 7w/4=6/3 | | 10p-3=2(12+4p)-4 | | 1+1+1+1+11+1+1+1+11+(1*0)+1=x | | 3x-1/x+1=0 | | 7m-5=4m+2 | | 10-3n=5(2-8n) | | 10p-3=2(12=4p)-7 | | x=1+1+1+1+11+1+1+1+11+(1*0)+1 | | 360=a+29+29+29 | | 75=3(−6n−5) | | -9+3/4n=-7.5 | | 5r-(1/5)=4/5 | | 9(y+2)=3(y–2) | | 3-5(c+4)=4 | | -1=7m=-6(-7+6m) | | 2/k-1-5k+1/k^2-1=-1/k+1 | | 2x-8-4x=3x-9-7 | | 3x=8=2 | | x=-11+1/2 | | 7h+7=2h-4 | | x=1+1+1+1+11+1+1+1+11+1*0+1 | | .2x2−x+2=0 | | -2(v+2)=20+v |

Equations solver categories